Comparison of two internal fixation systems in lumbar spondylolysis by finite element methods. (May 2022) - Li, Le; Jiang, Shuhao; Zhao, Junyong; Zhao, Mengmeng; Zhou, Xin; Li, Kunpeng; Liu, Chen; Zhang, Wencan; Chen, Junfei; Yu, Qun; Zhao, Yuefeng; Wang, Jingjing; et al.
Highlights: Finite element method was used to compare the internal fixation methods of lumbar spondylolysis. Two types of lumbar spondylolysis internal fixation systems: pedicle screw-U shape rod (PSUSR) and pedicle screw-vertebral plate hook (PSVPH) internal fixation systems. Based on CT images, four models are established by threshold segmentation and contour line reconstruction algorithm. After finite element analysis, the PSVPH internal fixation system has better biomechanical properties. Abstract: Background and purpose: Internal fixation surgeries are currently the most effective treatments for lumbar spondylolysis, but the optimal fixation method is still on debate. This study was designed to compare the biomechanical characteristics of two fixation methods for lumbar spondylolysis, the pedicle screw-U shape rod (PSUSR) internal fixation system, and the pedicle screw-vertebral plate hook (PSVPH) internal fixation system, through three-dimensional finite element analysis, expecting to provide clinical guidance. Methods: Four finite element models (A, B, C, D) of L4-S1 vertebral body of a female patient were reconstructed by CT image segmentation. (A: intact model. B: spondylolysis model. C: spondylolysis model with PSUSR internal fixation. D: spondylolysis model with PSVPH internal fixation). Six physiological motion states were simulated by applying 500N concentrated force and 10Nm moment load to four models. The biomechanical advantages of the two internal fixation systems were evaluated by comparing the range of motion (ROM), maximum stress, maximum strain, and maximum displacement of the models. Results: Compared to model B, the ROM decreased by 35.7%-57.1% in model C and 39.7%-64.8% in model D. The maximum displacements of model C and D both decreased. The maximum stresses in both vertebral and the internal fixation system are greater in model C than those in model D. The maximum stress and strain reduction of L5-S1 intervertebral disc in model D was greater than that in model C. Model D restores the articular cartilage stresses to the normal levels of model A. The maximum stress and maximum displacement of the bone graft in model C are greater than those in model D. Conclusions: The PSVPH internal fixation system has better biomechanical properties than PSUSR internal fixation system in several mechanical comparisons. Experimental results suggest that PSVPH internal fixation system can effectively treat lumbar spondylolysis while preserving segmental mobility, and can be the treatment of choice.